EVALUASI PRODUK PAVING BLOCK TIPE HOLLAND DARI BEBERAPA PRODUSEN DI KOTA SEMARANG - Wibowo, Titus Tonny; Mudiyono, Rachmat; Antonius, Antonius (Pondasi, 2024)
The inconsistency in the quality of paving blocks can result in uneven road surfaces, thereby increasing the risk of traffic accidents. This study aims to determine the compressive strength quality of Holland-type paving blocks from several producers in the city of Semarang, both those made manually and by machine, as well as to understand the reasons behind the dimensional inconsistencies of Holland-type paving blocks from various producers in the city. The research samples were taken from four paving block producers located in Semarang. The test results show that all paving block products from the four different producers meet or exceed the minimum compressive strength values set in SNI 03-0691-1998. This indicates that the products are theoretically capable of withstanding the applied compressive loads. The compressive strength test shows the lowest average value from producer AB at 17.21 MPa, while the highest average value was achieved by producer ADS at 19.3369 MPa. The dimensional inconsistencies of Holland-type paving blocks from several producers in Semarang can be attributed to various factors, including differences in production processes between producers, variations in the raw materials used, and differences in the settings of machines or production equipment.